Meningkatkan Prestasi Belajar Siswa Kelas XII IPS 1 Dengan Metode Pemberian Tugas Di Sekolah Menengah Atas Negeri 1 Muaro Jambi - Elizawati; journal journal (STIT Muhammadiyah Paciran Lamongan, 2019)
Abstract: The purposes of this study are to get bolstering about thestudents’ learning achievement in returning the paper task, toimprove students’ skill in doing theirs task, to increase responsibilityof students, to raise students interest, and to reach students’achievement in Geography learning in XII IPS 1 SMA Negeri 1Muaro Jambi. The data collected through observation,documentation and interview. Furthermore, the subjects of this studyconsisted of 27 students XII IPS 1 SMAN 1 Muaro Jambi. This studyrun from July to September 2014. The result of study displays thatthe paper task retirning method can improve students’ achievement.The sign of improvement is shown by improving students’s rate ingeography learning that starts from cycle 1 to cycle II. Anotherresult is this method can develop students’ interest in learning